Plato's Republic in the Islamic context new perspectives on Averroes's commentary - Orwin, Alexander (Rochester Studies in Medieval Political Thought,, 2022)
"The goal of the book is to provide an anthology covering the reception of Plato's Republic in the Islamic world, with a focus on Averroes's outstanding but underappreciated commentary on Plato's most famous dialogue. Despite the publication of Ralph Lerner's excellent English translation almost 50 years ago, very few scholarly studies have been written on it. We propose the following chapters, keeping in mind that some might be changed owing to collaboration with contributors"--